Diacylglycerol lipase activity in rod outer segments depends on the illumination state of the retina - Chamorro Aguirre, Estefania (2017)
The aim of the present research was to determine how the syn- thesis of endocannabinoid 2-arachidonoylglycerol (2-AG) for dia- cylglycerol lipase (DAGL) enzyme is modulated by the illumination state of the retina. DAGL activity was analyzed in purified rod outer segments (ROS) obtained from dark or light adapted retinas. Ret- inas were dissected from the eyes after dark or light adaptation. Dark-adapted bovine ROS (DROS) and bleached ROS (LROS) were purified by a discontinuous gradient of sucrose from retinas whose optic cup was either maintained under dim red light or exposed to light (3000 luxes) for 30 min. This activity was assayed using [3 H] glycerol-DAG as substrate and determined by [3 H]-MAG production. MAG was partially metabolized to glycerol by MAGL ac- tion. DAGL activity in LROS was higher than in DROS under all con- ditions assayed. When the enzyme activity was assayed in a range between 100 μg and 200 μg of ROS protein, [3 H]-MAG production was increased in LROS (p<0.01). However, the light effect on DAGL activity disappeared when 300 μg of protein were used. It was also observed that light increased DAGL activity at 1 and 2 hours of in- cubation. Interestingly, endocannabinoid production increased at 2 hours in DROS (p<0.001) and LROS (p<0.01) with respect to 1 hour of incubation. Additionally, it was observed that MAGL associated to DAGL activity was stimulated by light (p<0.01). The expression of cannabinoid receptors (CB1 and CB2) was also increased under light conditions. The data was analyzed using Student t-test, two way-ANOVA and Bonferroni test to compare different conditions. These results suggest a light effect on DAGL, the principal enzyme involved in 2-AG synthesis, as well as on the receptors to which this endocannabinoid binds to, thus indicating a potential role of 2-AG in phototransduction processes.